(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
It is known[1] that in silicon single crystals grown by the Czochralski method, the oxygen content can be controlled within (2 - 8) ×1017 cm-3 . In crystals grown by the FZ method (the crucible-less floating zone technique or "floating zone” method), both in vacuum and in the inert gas atmosphere, the oxygen content is less than 3×1016 cm-3 . Hence, it is clear why the properties of silicon with oxygen content in the range 3 × 1016 - 2 ×1017 cm-3 are least studied.